A Novel Approach to Enhancement Linked Laser Asymmetric Keratectomy Using Semi-Cylindrical Ablation Pattern in Patients with Myopic Regression After Laser Refractive Surgery - Min JS (Dove Medical Press, 2021)
Ji Sang Min,1 Byung Moo Min2 1Kim’s Eye Hospital, Division of Cornea, Cataract, and Refractive Surgery, Konyang University School of Medicine, Seoul, South Korea; 2Woori Eye Clinic, Department of Ophthalmology, Yonsei University School of Medicine, Daejon, South KoreaCorrespondence: Byung Moo MinWoori Eye Clinic, Department of Ophthalmology, Yonsei University School of Medicine, Daeduk Daero 219 (Dunsan-dong), Seo-gu, Daejon, 35229, South KoreaTel +82-42-476-1675Fax +82-42-476-1670Email bmin8275@naver.comPurpose: We aimed to introduce a new technique to reduce regional asymmetry of corneal thickness by assessing its effectiveness in four patients with myopic regression after laser refractive surgery (LRS).Patients and Methods: Four patients (four eyes) with myopic regression after LRS were included in this study. A new technique of enhancement with laser epithelial keratomileusis-linked laser asymmetric keratectomy using semi-cylindrical ablation pattern (E-LAK-SCAP) with full integration of the Vision-Up software for analyzing the corneal thickness deviation can be used to create central symmetry by blocking laser ablation on the thin cornea. It reduces the regional asymmetry of the corneal thickness, thus improving corneal symmetry and correcting the refractive power and myopic shift due to E-LAK-SCAP. We measured refraction, visual acuity, intraocular pressure (IOP), central corneal thickness (CCT), corneal irregularities in the 3.0mm, and 5.0 zones on Orbscan maps, the sum of corneal thickness deviations in four directions (SUM), distance between the maximum posterior elevation (best-fit-sphere [BFS]) and the visual axis (DISTANCE), and angle kappa before and after LRS and E-LAK-SCAP. Blurring scores were measured before and after E-LAK-SCAP.Results: The uncorrected far visual acuity (LogMAR) increased after LRS and E-LAK-SCAP. SUM (μm) increased after LRS in three cases, but decreased in all four cases after E-LAK-SCAP. DISTANCE increased after LRS, but decreased after E-LAK-SCAP. The spherical equivalent, CCT, decreased after LRS and E-LAK-SCAP. Blurring scores decreased after E-LAK-SCAP, and angle kappa was similar before and after LRS, but decreased after E-LAK-SCAP. IOP was similar before and after both LRS and E-LAK-SCAP.Conclusion: E-LAK-SCAP improved corneal symmetry by reducing the SUM and DISTANCE, showing good postoperative visual acuity, and blurring was reduced postoperatively. There was no myopic regression in the one-year postoperative period.Keywords: regional asymmetry of corneal thickness, myopic regression, LRS, E-LAK-SCAP